2022
DOI: 10.1038/s41588-021-00976-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the human microglial transcriptome across brain regions, aging and disease pathologies

Abstract: Microglia have emerged as important players in brain aging and pathology. To understand how genetic risk for neurological and psychiatric disorders is related to microglial function, large transcriptome studies are essential. Here, we describe the transcriptome analysis of 255 primary human microglia samples isolated at autopsy from multiple brain regions of 100 human subjects. We performed systematic analyses to investigate various aspects of microglial heterogeneities, including brain region and aging. We ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
119
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(142 citation statements)
references
References 109 publications
5
119
0
Order By: Relevance
“…Green: The CELF1 locus was associated with AD in genome-wide association studies (Ref. [3][4][5][6]. Red: Transcriptomic studies using CELF1 knockdown revealed strong regulation of KLC1 by CELF1; cross-linking and immunoprecipitation sequencing identified KLC1 RNA as a binding partner of the CELF1 protein and revealed its binding site.…”
Section: Fig 6 Hypothesis-free Omics Approaches Identified a Molecula...mentioning
confidence: 99%
See 2 more Smart Citations
“…Green: The CELF1 locus was associated with AD in genome-wide association studies (Ref. [3][4][5][6]. Red: Transcriptomic studies using CELF1 knockdown revealed strong regulation of KLC1 by CELF1; cross-linking and immunoprecipitation sequencing identified KLC1 RNA as a binding partner of the CELF1 protein and revealed its binding site.…”
Section: Fig 6 Hypothesis-free Omics Approaches Identified a Molecula...mentioning
confidence: 99%
“…As a result, there has been precipitous increase in the number of associated loci and genes identified whose function in disease is unknown 1 . Many researchers have suggested that the innovative use of functional omics will be crucial to interpret GWAS results and reveal molecular pathways in complex diseases in the post-GWAS era, but concrete strategies are still being explored 1,2,3,4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preponderance of human genetics evidence has shed light on a number of common and rare genetic loci closely associated with AD risk. Notably, many of these risk loci are associated with genes that have been reported as microglia specific or highly expressed in microglia relative to other cell types in the central nervous system (CNS) (Lopes et al, 2022; Verheijen and Sleegers, 2018). This broad trend implicates microglia, as the predominant immune cells residing in the brain parenchymal have emerged as crucial players in the pathogenesis of AD.…”
Section: Introductionmentioning
confidence: 99%
“…In neuroinflammation, microglia become activated, undergo a change in morphology, and release various cytotoxic mediators. Microglia are thought to be important factors in brain aging and pathologies, including Alzheimer’s and Parkinson’s [ 8 , 9 ]. They are known to release pro-inflammatory cytokines, such as TNF α , when activated, as well as potentially neurotoxic substances, such as nitric oxide.…”
Section: Introductionmentioning
confidence: 99%